2018
DOI: 10.1002/cncr.31542
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing colorectal cancer screening by race and sex: Microsimulation analysis II to inform the American Cancer Society colorectal cancer screening guideline

Abstract: BACKGROUNDColorectal cancer (CRC) risk varies by race and sex. This study, 1 of 2 microsimulation analyses to inform the 2018 American Cancer Society CRC screening guideline, explored the influence of race and sex on optimal CRC screening strategies.METHODSTwo Cancer Intervention and Surveillance Modeling Network microsimulation models, informed by US incidence data, were used to evaluate a variety of screening methods, ages to start and stop, and intervals for 4 demographic subgroups (black and white males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 46 publications
(77 reference statements)
0
70
0
2
Order By: Relevance
“…To gain additional understanding of outcomes associated with different screening strategies (particularly starting age) for black and white adults, the ACS commissioned a modeling study by the MISCAN and SimCRC investigators (2 of the CISNET modeling groups) that extended the previous analysis conducted for the USPSTF. The objective was to assess the potential benefit (life‐years gained and CRC deaths averted) and the burden of different CRC screening strategies for black and white women and men . Subsequently, the GDG determined that recent evidence demonstrating a significant increase in CRC incidence among individuals younger than 55 years, which was attributable to a strong birth‐cohort effect, warranted a reevaluation of the optimal age to start screening in the average‐risk population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain additional understanding of outcomes associated with different screening strategies (particularly starting age) for black and white adults, the ACS commissioned a modeling study by the MISCAN and SimCRC investigators (2 of the CISNET modeling groups) that extended the previous analysis conducted for the USPSTF. The objective was to assess the potential benefit (life‐years gained and CRC deaths averted) and the burden of different CRC screening strategies for black and white women and men . Subsequently, the GDG determined that recent evidence demonstrating a significant increase in CRC incidence among individuals younger than 55 years, which was attributable to a strong birth‐cohort effect, warranted a reevaluation of the optimal age to start screening in the average‐risk population.…”
Section: Methodsmentioning
confidence: 99%
“…Additional modeling analyses by the MISCAN investigators incorporated recent Surveillance, Epidemiology, and End Results (SEER) incidence data and evaluated screening outcomes for the general US population . Analyses of outcomes for race‐specific and sex‐specific groups by MISCAN and SimCRC, which initially were carried out under the assumption of stable incidence, were repeated to incorporate recent SEER incidence data …”
Section: Methodsmentioning
confidence: 99%
“…Although there is very limited empirical evidence on screening outcomes in adults younger than 50 years (because of the traditional starting age of 50 years in research studies and clinical practice), the qualified recommendation that average‐risk adults begin screening at age 45 years is based on the prolonged trends in disease burden showing increases in CRC incidence and mortality in adults younger than 55 years and modeling analyses showing efficient strategies for CRC screening starting at age 45 years . The underlying evidence pertaining to rising incidence in adults younger than 55 years was discussed in detail in the guideline article and was summarized in last year's annual cancer screening update …”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
“…However, when the ACS Guideline Development Group was evaluating the evidence to determine whether a younger age to start screening should be recommended for blacks as well as American Indians and Alaska Natives, it became evident that the incidence rate of CRC for individuals younger than 50 years was no longer higher in blacks compared with whites . On the basis of this observation, the ACS evaluated simulations of CRC screening scenarios by age, sex, and ethnicity using 2 of the 3 Cancer Intervention and Surveillance Modeling Network models that also were used by the USPSTF but were modified to reflect the higher incidence observed in younger cohorts and expected to carry forward into the age groups targeted for screening . When the models were refined with the updated incidence data, 2 microsimulation models predominately indicated that screening scenarios with a starting age of 45 years had more favorable efficiency ratios than scenarios in which screening started at age 50 years.…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%
“…The age of 45 years to initiate CRC screening in average‐risk adults is the most significant change from previous ACS CRC screening guidelines . The recommendation for an earlier starting age was based on the prolonged trends in disease burden showing increases in CRC incidence and mortality in persons under age 50 years and modeling analyses showing efficient strategies for CRC screening starting at age 45 years …”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%